Employee Development Strategy To Improve Services in Facing Bank 4.0 at Bank XYZ Region Jakarta 3 - Hary Kurniawan; M. Syamsul Ma’arif; Siti Jahroh (School of Business, Bogor Agricultural University (SB-IPB), 2025)
Background: The banking industry in the future will face increasingly complex, diverse, and ever-changing challenges. Rapid advances in information technology have ushered global society into a new era known as Industrial Revolution 4.0. In the development of digital transformation, there are challenges where the development and potential of human resources have not been balanced with adequate skills, so human resource development is an interesting topic for further research. Purpose: This study aims to analyze the internal and external factors of employee development strategy, formulate strategies for employee development, and determine the priority strategies for employee development using SWOT and QSPM.Design/methodology/approach: Based on this background, this research aims to analyze internal and external factors in employee development strategies, formulate strategies for employee development, and determine priority strategies for employee development. Next, to determine employee development strategies, researchers conducted an analysis using the SWOT method and determined priority strategies using QSPM. Finding/Result: The results of the SWOT analysis test in this research contained eight strategies. Meanwhile, the priority strategy in employee development based on the QSPM method is to increase employee competency by focusing on a self-learning culture through a digital learning platform so that they can develop new features or improve existing features on products and improve digital services and implement a culture of innovation and continuous improvement in the entire line.Conclusion: This study found employee development strategies to enhance in addressing Bank 4.0 by improving employee competencies, focusing on a self-learning culture through digital learning platforms to develop new features or improve exciting ones on products, and enhancing digital services and implementing a culture of innovation and continuous improvement across all areas.Originality/value (State of art): This study uses IFE dan EFE with VRIO and PESTLE tools. Keywords: IFE, EFE, Employee performance, QSPM, SWOT